Land‒atmosphere coupling effects of soil temperature and moisture on extreme precipitation in the arid regions of Northwest China - Wu, Shuting; Wei, Zhigang; Li, Xianru; Ma, Li (Frontiers in Earth Science, 2023)
With global warming and more frequent extreme precipitation events in recent years, the phenomenon of warming and humidification in the arid regions of Northwest China (ANWC) has attracted increasing attention. We assessed the coupling effects of soil temperature and moisture on extreme precipitation in the ANWC by using daily precipitation data from CN05.1 and monthly data on soil temperature, soil moisture, and energy from ERA5-land, 1961-2018. After logical partitioning by K-means clustering, the primary influencing routes in each partition were investigated using two indices of extreme precipitation, indicated by precipitation on very wet days (R95P) and the number of extreme precipitation days (R10day). We found that (1) Local extreme precipitation has had a steadily growing impact on overall precipitation. In summer, this impact is primarily driven by an increase in the quantity of extreme precipitation, but in winter, it is primarily driven by an increase in the intensity of single precipitation. (2) The Tianshan Mountains (TM) and Qilian Mountains (QM) are the key locations for the coupling of soil temperature and moisture with the extreme precipitation index. Both locations exhibit a positive coupling state for soil temperature with extreme precipitation with positive coupling in the TM but negative coupling in the QM for soil moisture with extreme precipitation. (3) In the coupling of soil temperature and moisture with energy, the relevant significant regions are almost all over the ANWC throughout the year and all seasons, and the coupling high-value areas are concentrated around the basin. (4) In the TM–Hami Basin (HB)–QM, the coupling between energy and the extreme precipitation index is also stronger. The specific coupling paths have been changing with seasonal and regional changes.